Review on Architecture of Computer Networks - C Mathew, Jincy (International Journal of Psychosocial Rehabilitation, 2020)
The Open Systems Interconnection model (OSI model) is a product of the International Organization for Standardization. An OSI reference model is a conceptual blueprint of how communication should take place. It is a way of subdividing a communications system into smaller parts called layers. A layer is a collection of conceptually similar functions that provide services to the layer above it and receive services from the layer below it. When a communication system is designed in this manner, it is known as layered architecture. It’s a set of guidelines that application developers use to create and implement applications that run on a network. It also provides a framework for creating and implementing networking standards, devices, and internetworking schemes. This paper explains the OSI Reference Model, which comprises seven different layers. Each layer is having its own responsibilities.